2006
DOI: 10.1111/j.1471-4159.2006.04291.x
|View full text |Cite
|
Sign up to set email alerts
|

p53‐dependent neuronal cell death in a DJ‐1‐deficient zebrafish model of Parkinson's disease

Abstract: Mutations in DJ-1 lead to early onset Parkinson's disease (PD). The aim of this study was to elucidate further the underlying mechanisms leading to neuronal cell death in DJ-1 deficiency in vivo and determine whether the observed cell loss could be prevented pharmacologically. Inactivation of DJ-1 in zebrafish, Danio rerio, resulted in loss of dopaminergic neurons after exposure to hydrogen peroxide and the proteasome inhibitor MG132. DJ-1 knockdown by itself already resulted in increased p53 and Bax expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
116
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(132 citation statements)
references
References 43 publications
12
116
2
1
Order By: Relevance
“…This suggests that DJ-1 does not function downstream of caspase-8 activation or its effector caspases and their substrates. It has been reported that DJ-1 inhibits apoptosis by regulating different transcription factors to modulate gene expression (Clements et al, 2006;Bretaud et al, 2007;Fan et al, 2008a;Vasseur et al, 2009;Foti et al, 2010). However, we observed that DJ-1 did not affect DR mRNA or protein levels in H1299 cells (Figure 3).…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…This suggests that DJ-1 does not function downstream of caspase-8 activation or its effector caspases and their substrates. It has been reported that DJ-1 inhibits apoptosis by regulating different transcription factors to modulate gene expression (Clements et al, 2006;Bretaud et al, 2007;Fan et al, 2008a;Vasseur et al, 2009;Foti et al, 2010). However, we observed that DJ-1 did not affect DR mRNA or protein levels in H1299 cells (Figure 3).…”
Section: Discussionmentioning
confidence: 53%
“…To explore the role of DJ-1 in the TRAIL-induced apoptosis pathway, we performed DJ-1 knockdown experiments. Because DJ-1 is involved in regulating p53 activity (Bretaud et al, 2007;Fan et al, 2008a, b;Giaime et al, 2010), we performed experiments using both p53 þ / þ and p53À/À human colon cancer cells (HCT116) to determine whether p53 is involved in the DJ-1-regulated TRAIL pathway. Smallinterfering RNA against DJ-1 (siDJ-1) caused a reduction of approximately 70% of endogenous DJ-1 compared with transfections using a negative control small-interfering RNA (siNC; Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent report, knockdown of DJ-1 in zebrafish model of Parkinson's disease resulted in increased expression of p53 and Bax, suggesting that absence of DJ-1 activates the death pathway (Bretaud et al, 2007). Our finding that DJ-1 is phosphorylated upon activation of p53 raises the possibility that p53-dependent phosphorylation of DJ-1 inhibits its function and thus facilitates apoptosis.…”
supporting
confidence: 59%